MENINGKATKAN HASIL BELAJAR SAINS DENGAN MODEL PEMBELAJARAN KOOPERATIF - Boy, Bonefasius Yanwar; Panda, Florentina Maria (Magister Pendidikan IPA, UNCEN, 2013)
Classroom Action Research (PTK) conducted in this study for the material temperature, is focused on cooperative learning model. PTK performed in two cycles. The treatment cycle by implementing Cooperative Learning I, are given materials on the temperature at which the students after it is divided into cooperative groups, then discuss the matter temperature and answering the questions. After the learning process in cooperative groups conducted for the answer and deduce the results of the discussion. While on the cycle II do cooperative learning model using experimental methods and teaching tools such as worksheets, tools and materials in the experiment. The results of use of cooperative learning model with the experimental method at the temperature of the subject helps students to be more active and creative. The results showed that the exhaustiveness of the cycle I amounting to 63.88% and the cognitive value of the average 58.47 and the cycle II with 83.3% completeness and cognitive value of the average 68.75. Key words: Learning Outcomes, Cooperative Learning Model, Student, Junior High School